Superconducting Nanostrip Photon-Number-Resolving Detector as an Unbiased Random Number Generator - Pasquale Ercolano; Mikkel Ejrnaes; Ciro Bruscino; Syed Muhammad Junaid Bukhari; Daniela Salvoni; Chengjun Zhang; Jia Huang; Hao Li; Lixing You; Loredana Parlato; Giovanni Piero Pepe (IEEE Transactions on Quantum Engineering)
Detectors capable of resolving the number of photons are essential in many applications, ranging from classic photonics to quantum optics and quantum communication. In particular, photon-number-resolving detectors based on arrays of superconducting nanostrips can offer a high detection efficiency, a low dark count rate, and a recovery time of a few nanoseconds. In this work, we use a detector of this kind for the unbiased generation of random numbers by following two different methods based on the detection of photons. In the former, we exploit the property that the light is equally distributed on each strip of the entire detector, whereas in the latter, we exploit the fact that, for a high average number of photons, the parity of the Poisson distribution of the number of photons emitted by the laser tends to be zero. In addition, since these two methods are independent, it is possible to use them at the same time.